Sinergi Kapabilitas Finansial, Modal Sosial, dan Modal Spiritual dalam Membangun Keberlanjutan Lembaga Perkreditan Desa Berbasis Adat di Bali - Kustina, Ketut Tanti; Septiani, Ni Kadek Ayu Putri; Dewi, Putu Purnama; Prena, Gine Das (Juara: Jurnal Riset Akuntansi, 2025)
The Triple Bottom Line (TBL) approach emphasizes business sustainability in three aspects: economic profit, social people, and environmental planet. From an economic perspective, LPD sustainability is determined by solid financial capability in managing assets and liabilities effectively. Social capital strengthens public trust and community involvement, while spiritual capital forms ethical values ​​and concern for the environment. This study examines the influence of financial capability, social capital, and spiritual capital on LPD business sustainability. Data were obtained from 115 respondents in 23 LPDs through a purposive sampling method and analysis was carried out using multiple linear regression. The results of the study indicate that the three variables have a positive and significant influence, partially or simultaneously, when faced with business sustainability. These findings indicate that strengthening financial capacity, building trust-based social networks, and implementing spiritual values ​​are important pillars in supporting LPD sustainability.